Transformasi Al-Qur’an dan Nalar Logis Otentisitas Al-Qur’an - Saputro, Oscar Wardhana Windro (STAI Ali bin Abi Thalib Surabaya, 2024)
This study aims to explore more recent and accurate information about the doubts that arise about the authenticity of the Qur'an and scientific explanations that can answer these doubts. This research uses a qualitative approach with the type of library research. The data sources that are the main discussion and are directly related to this research are in the form of books on the history and 'ulu>m al-Qur'an as well as articles about it and also regarding criticism of the Qur'an, which are also taken from journals, websites and other scientific articles. In Islam, the Qur'an is a holy book that is believed to be authentic by its adherents and is one of the pillars of faith that determines the validity of one's faith. However, the transformation process of the Qur'an that has taken place for centuries has not escaped some criticism about its authenticity as the word of God. The results of this study that the transmission and transformation of the Qur'an occurred in several phases: revelation; collection during the Prophet's time; collection during Abu Bakr's time; collection during Uthman bin 'Affan's time; and the period of perfecting the Mushaf script. Each phase was criticized for its authenticity in terms of the method and form of revelation, the process of collecting the Qur'an, writing the Mushaf rasm, and other aspects. Islamic scholars responded to the criticism with historical data, logical reasoning, and arguments that establish the Qur'an's authenticity despite its transmission and transformation.